AN INEXPENSIVE METHOD TO MEASURE KNEE EXTENSORS' POWER IN OLDER ADULTS - Pinho,João Pedro (2015)
Introduction: Measuring knee extensors' power in elderly population is crucial but not accessible to everyone. Objective: To provide a method to calculate knee extensors' power in a conventional knee extension machine. Method: Thirteen sedentary elderly women (69.3±4.1 years) performed six knee extensions as fast as possible. Kinematic data, an anthropometric model and Newtonian mechanics was used to write movement equations that allowed calculating knee extensors' power and work. The reliability was assessed by variables' coefficient of variation, intraclass correlation coefficient and standard measurement error. Results: Knee extensors' peak power and work values obtained were in agreement with the literature. We found high intraclass ICC values for both variables (93% and 97%, respectively) and low normalized SEM (10.13% and 2.09%, respectively). Conclusion: We provided an inexpensive method to assess a major physical dysfunction indicator in older adults which can also be used to evaluate the progression of an intervention.